Analisis Pengaruh Kemudahan Penggunaan Aplikasi Dan Pengalaman Berbelanja Terhadap Minat Beli Secara Online Pada Situs E-Commerce Shopee - Firdaus Algadri; Indah Ariffianti; Ulfiyani Asdiansyuri (Kredibel: Jurnal Ilmiah Manajemen, 2024)
This study aims to analyze the effect of ease of use of applications and shopping experience on online buying interest in shopee e-commerce sites (case study of Sekolah Tinggi Ilmu Ekonomi AMM Mataram students). Type associative research. Population were Sekolah Tinggi Ilmu Ekonomi AMM Mataram students. sample used 97 respondents. Data collection technique used questionnaire. Data analysis using multiple linear regression analysis shows (Y = 5.921 + 0.206X1 + 0.425X2). Based on results of hypothesis testing partially ease of use of the application does not have significant effect on buying interest with t value 1.703 < t table 1.985, and shopping experience has significant effect on buying interest with t value 3.497 > t table 1.985. Simultaneously ease of use of the application, shopping experience has significant effect on buying interest with F count 17.348> F count 3.09 with significance of 0.000. Shopping experience is most dominant variable affecting buying interest with beta value 0.385.